Cultures of Improvement in Scottish Romanticism, 1707-1840 - Benchimol, Alex; McKeever, Gerard Lee (Taylor & Francis, 2018)
The first applied research volume in Scottish Romanticism, this collection foregrounds the concept of progress as 'improvement' as a constitutive theme of Scottish writing during the long eighteenth century. It explores improvement as the animating principle behind Scotland's post-1707 project of modernization, a narrative both shaped and reflected in the literary sphere. It represents a vital moment in Romantic studies, as a 'four-nations' interrogation of the British context reaches maturity. Equally, the volume contributes to a central concern in the study of Scottish culture, amplifying a critical synthesis of Romanticism and Enlightenment. Chapter 9 of this book is freely available as a downloadable Open Access PDF under a Creative Commons Attribution-Non Commercial-No Derivatives 3.0 license. https://s3-us-west-2.amazonaws.com/tandfbis/rt-files/docs/Open+Access+Chapters/9781351056427_oachapter9.pdf